Dissociable Somatotopic Representations of Chinese Action Verbs in the Motor and Premotor Cortex - Wu, Haiyan (Sci Rep, 2013)
The embodied view of language processing holds that language comprehension involves the recruitment of sensorimotor information, as evidenced by the somatotopic representation of action verbs in the motor system. However, this review has not yet been examined in logographic scripts such as Chinese, in which action verbs can provide explicit linguistic cues to the effectors (arm, leg, mouth) that conduct the action (hit, jump, drink). We compared the somatotopic representation of Chinese verbs that contain such effector cues and those that do not. The results showed that uncued verbs elicited similar somatotopic representation in the motor and premotor cortex as found in alphabetic scripts. However, effector-cued verbs demonstrated an inverse somatotopic pattern by showing reduced activation in corresponding motor areas, despite that effector-cued verbs actually are rated higher in imageability than uncued verbs. Our results support the universality of somatotopic representation of action verbs in the motor system.